SISI GELAP EKSPLOITASI ANAK BAWAH UMUR DI KOTA PEKANBARU - M.Zulherawan; Syahrul Akmal Latief (SISI LAIN REALITA, 2020)
Every child has the right to survival in terms of the nation and state, children are the future of the nation and the next generation of the ideals of the nation so that they have the right to survive, develop, grow, participate and are entitled to protection from acts of violence and discrimination as well as civil rights and freedoms. The high rate of exploitation of minors in Pekanbaru is one of the things that makes us pay attention to the splendor of the development side of the city of Pekanbaru which leads to civility. The black side of exploitation of underage children makes as citizens we are obliged to socialize the existence of the Child Protection Act, especially on the threat of criminal acts of employing children. We can also socialize human rights to parents. Early prevention at the family level can reduce the effects of children becoming victims of exploitation. There is also a formulation of the problem raised in this research which is "What is the background of the formation of the exploitation of basic age children in Pekanbaru City?". The research procedure used in this research is a qualitative method by collecting information by associating as many as 15 informants, namely 7 key informants and 8 informants whose results from the study were analyzed using the Atlas application system. IT is useful for classifying information experienced in the field. The results that the author has are the presence of actors who are motivated to carry out exploitation, appropriate targets for exploitation and the lack of supervision regarding the exploitation of these children. And the aspects behind the formation of exploitation of minors are economic aspects, coercion from parents, culture and the absence of care. In order to minimize this problem, it is hoped that the related service and the Civil Service Police Unit will carry out patrols more often and residents will participate in overcoming these problems.